Measuring the Social Impact of Burns on Survivors. Issue 1 (January 2017) - Marino, Molly; Soley-Bori, Marina; Jette, Alan M.; Slavin, Mary D.; Ryan, Colleen M.; Schneider, Jeffrey C.; Acton, Amy; Amaya, Flor; Rossi, Melinda; Soria-Saucedo, Rene; Resnik, Linda; Kazis, Lewis E.
Abstract : Many burn survivors experience social challenges throughout their recovery. Measuring the social impact of a burn injury is important to identify opportunities for interventions. The aim of this study is to develop a pool of items addressing the social impact of burn injuries in adults to create a self-reported computerized adaptive test based on item response theory. The authors conducted a comprehensive literature review to identify preexisting items in other self-reported measures and used data from focus groups to create new items. The authors classified items using a guiding conceptual framework on social participation. The authors conducted cognitive interviews with burn survivors to assess clarity and interpretation of each item. The authors evaluated an initial pool of 276 items with burn survivors and reduced this to 192 items after cognitive evaluation by experts and burn survivors. The items represent seven domains from the guiding conceptual model: work, recreation and leisure, relating to strangers, romantic, sexual, family, and informal relationships. Additional item content that crossed domains included using self-comfort and others' comfort with clothing, telling one's story, and sense of purpose. This study was designed to develop a large item pool based on a strong conceptual framework using grounded theory analysis with focus groups of burn survivors and their caregivers. The 192 items represent 7 domains and reflect the unique experience of burn survivors within these important areas of social participation. This work will lead to developing the Life Impact Burn Recovery Evaluation profile, a self-reported outcome measure.